2021
DOI: 10.2147/ijn.s322894
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Theranostics of Magnetic Resonance Imaging and Photothermal Therapy of Breast Cancer Based on the Janus Nanostructures Fe3O4-Aushell-PEG

Abstract: Background Satisfactory prognosis of breast cancer (BC) is limited by difficulty in early diagnosis and insufficient treatment. The combination of molecular imaging and photothermal therapy (PTT) may provide a solution. Methods Fe 3 O 4 -Au shell nanoparticles (NPs) were prepared by thermal decomposition, seeded growth and galvanic replacement and were comprehensively characterized. After c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…Surface functionalization of the MNPs is also an effective parameter in adjusting the r2 (inverse of T2)/r1 (inverse of T1) value. In this matter, PEG‐coated Au‐Fe 3 O 4 JNPs have been investigated as a contrast agent in a concentration‐dependent manner in MRI by Kang et al (2021). By decreasing the T2, darker images are obtained with the increase in concentration.…”
Section: Magnetic Janus Nps and Micro‐/nanomotors In Biomedical Appli...mentioning
confidence: 99%
“…Surface functionalization of the MNPs is also an effective parameter in adjusting the r2 (inverse of T2)/r1 (inverse of T1) value. In this matter, PEG‐coated Au‐Fe 3 O 4 JNPs have been investigated as a contrast agent in a concentration‐dependent manner in MRI by Kang et al (2021). By decreasing the T2, darker images are obtained with the increase in concentration.…”
Section: Magnetic Janus Nps and Micro‐/nanomotors In Biomedical Appli...mentioning
confidence: 99%
“…After six days, except for black scars, almost no tumour was observed. 125 All the above studies have shown that PTT has a significant clinical effect on the treatment of breast cancer, and compared with traditional surgery, it has evident characteristics, such as less trauma and fast recovery of patients.…”
Section: Ptt and Its Anticancer Researchmentioning
confidence: 99%
“…Once irradiated by light of a specific wavelength, the PTT agents absorb photon energy, migrating from the ground singlet state (S 0 ) to an excited singlet state (S 1 ). As the S 1 state PTT agents return to the S 0 state, they must undergo vibrational relaxation, a nonradiative form of decay that results in collisions between the excited photothermal agents and their surrounding molecules (38). This increased kinetic energy increases the surrounding microenvironment temperature (Figure 2A).…”
Section: Role Of Ptt In Cancer Immunotherapymentioning
confidence: 99%